1999
DOI: 10.1029/98ja02830
|View full text |Cite
|
Sign up to set email alerts
|

Finding gravity wave source positions using the Super Dual Auroral Radar Network

Abstract: Abstract. Through the groundscatter process the Super Dual Auroral Radar (Super-DARN) has become a powerful tool for studying F region gravity waves. However, the measurement of the gravity wave position is not direct and relies on an assumption relating ground scatter distance to reflection distance. In previous studies it has been assumed that the tilting of the ionospheric reflecting layer was negligible. Hence the gravity wave distance has been calculated as if the reflecting layer was strictly horizontal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 11 publications
(11 reference statements)
6
31
0
Order By: Relevance
“…Using this method it was found that waves typically originated near the convection reversal boundary, with the majority of the waves originating within the eastward electrojet in the afternoon sector ionosphere. However, under some circumstances the position of the wave source, determined by simple assumptions about the radio propagation path, can lead to errors of up to 30% in the range determination (Hall et al 1999;MacDougall et al 2001). Further study of wave parameters and source locations confirmed that the Earth-reflected model proposed by Samson et al (1990) adequately described the gravity wave observations of the Goose Bay SuperDARN radar (Bristow et al 1994;Huang et al 1998a;Hall et al 1999).…”
Section: Gravity Wavesmentioning
confidence: 56%
See 1 more Smart Citation
“…Using this method it was found that waves typically originated near the convection reversal boundary, with the majority of the waves originating within the eastward electrojet in the afternoon sector ionosphere. However, under some circumstances the position of the wave source, determined by simple assumptions about the radio propagation path, can lead to errors of up to 30% in the range determination (Hall et al 1999;MacDougall et al 2001). Further study of wave parameters and source locations confirmed that the Earth-reflected model proposed by Samson et al (1990) adequately described the gravity wave observations of the Goose Bay SuperDARN radar (Bristow et al 1994;Huang et al 1998a;Hall et al 1999).…”
Section: Gravity Wavesmentioning
confidence: 56%
“…However, under some circumstances the position of the wave source, determined by simple assumptions about the radio propagation path, can lead to errors of up to 30% in the range determination (Hall et al 1999;MacDougall et al 2001). Further study of wave parameters and source locations confirmed that the Earth-reflected model proposed by Samson et al (1990) adequately described the gravity wave observations of the Goose Bay SuperDARN radar (Bristow et al 1994;Huang et al 1998a;Hall et al 1999). Examination of a large number of events showed waves with frequencies mainly between 0.3 mHz and 0.5 mHz, and wavelengths that ranged between 160 km and 560 km.…”
Section: Gravity Wavesmentioning
confidence: 99%
“…This modeling assumes that we know the antenna pattern and that there is no absorption. Doing this modeling showed that the formula used in Hall et al (1999) had backscatter that was too strong for low elevation angles. Accordingly the formula was modi®ed for this study and for elevation angles less than 60°(the angles of importance for this study) the backscatter coe cient, relative to 0 dB for specular re¯ection, was taken as r = )30.0 + 1.0´(elevationangle )60.0) dB.…”
Section: Tid Simulationsmentioning
confidence: 99%
“…Hall et al (1999) adapted a typical backscatter formula from formulas applicable to much higher frequencies. For the present study the observed backscatter for an unperturbed ionosphere was examined.…”
Section: Tid Simulationsmentioning
confidence: 99%
See 1 more Smart Citation